A candidate sex determination locus in amphibians which evolved by structural variation between X- and Y-chromosomes - Kuhl, Heiner; Tan, Wen Hui; Klopp, Christophe; Kleiner, Wibke; Koyun, Baturalp; Ciorpac, Mitica; Feron, Romain; Knytl, Martin; Kloas, Werner; Schartl, Manfred; Winkler, Christoph; Stöck, Matthias (Nature communications, 2024)
Most vertebrates develop distinct females and males, where sex is determined by repeatedly evolved environmental or genetic triggers. Undifferentiated sex chromosomes and large genomes have caused major knowledge gaps in amphibians. Only a single master sex-determining gene, the dmrt1-paralogue (dm-w) of female-heterogametic clawed frogs (Xenopus; ZW♀/ZZ♂), is known across >8740 species of amphibians. In this study, by combining chromosome-scale female and male genomes of a non-model amphibian, the European green toad, Bufo(tes) viridis, with ddRAD- and whole genome pool-sequencing, we reveal a candidate master locus, governing a male-heterogametic system (XX♀/XY♂). Targeted sequencing across multiple taxa uncovered structural X/Y-variation in the 5'-regulatory region of the gene bod1l, where a Y-specific non-coding RNA (ncRNA-Y), only expressed in males, suggests that this locus initiates sex-specific differentiation. Developmental transcriptomes and RNA in-situ hybridization show timely and spatially relevant sex-specific ncRNA-Y and bod1l-gene expression in primordial gonads. This coincided with differential H3K4me-methylation in pre-granulosa/pre-Sertoli cells, pointing to a specific mechanism of amphibian sex determination.
Keywords: Animals; chromozom X; Y Chromosome; Female; transkripční faktory; Amphibians; RNA, Untranslated; ženské pohlaví; procesy určující pohlaví; genom; Transcription Factors; Genome; Evolution, Molecular; molekulární evoluce; obojživelníci; nekódující RNA; Male; X Chromosome; Sex Determination Processes; mužské pohlaví; zvířata; chromozom Y